A model for the provision of clerical and administrative personnel in the Provincial Administration of the Cape of Good Hope - Roach, T. L.(Trevor Lourens) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.P.A.) -- University of Stellenbosch, 1984.